A transcriptomic analysis of neuropathic pain in the anterior cingulate cortex after nerve injury. Issue 2 (1st February 2022) - Zhang, Yu; Jiang, Shiwei; Liao, Fei; Huang, Zhifeng; Yang, Xin; Zou, Yu; He, Xin; Guo, Qulian; Huang, Changsheng
ABSTRACT: The anterior cingulate cortex (ACC) is a core brain region processing pain emotion. In this study, we performed RNA sequencing analysis to reveal transcriptomic profiles of the ACC in a rat chronic constriction injury (CCI) model. A total of 1628 differentially expressed genes (DEGs) were identified by comparing sham-operated rats with rats of 12 hours, 1, 3, 7, and 14 days after surgery, respectively. Although these inflammatory-related DEGs were generally increased after CCI, different kinetics of time-series expression were observed with the development of neuropathic pain affection. Specifically, the expression of Ccl5, Cxcl9 and Cxcl13 continued to increase following CCI. The expression of Ccl2, Ccl3, Ccl4, Ccl6, and Ccl7 were initially upregulated after CCI and subsequently decreased after 12 hours. Similarly, the expression of Rac2, Cd68, Icam-1, Ptprc, Itgb2, and Fcgr2b increased after 12 hours but reduced after 1 day. However, the expression of the above genes increased again 7 days after CCI, when the neuropathic pain affection had developed. Furthermore, gene ontology analysis, Kyoto Encyclopedia of Genes and Genomes pathway enrichment and interaction network analyses further showed a high connectivity degree among these chemokine targeting genes. Similar expressional changes in these genes were found in the rat spinal dorsal horn responsible for nociception processing. Taken together, our results indicated chemokines and their targeting genes in the ACC may be differentially involved in the initiation and maintenance of neuropathic pain affection. These genes may be a target for not only the nociception but also the pain affection following nerve injury.